Voltammetric Sensing System for the Detection of Cholesterol Based on the Ni-Bisurea-Pyrographite Composite; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Lukina A. A. Anastasia; Ismailov D. V. Daniar; Ilyin A. P. Aleksandr Petrovich; Derina K. V. Kseniya Vladimirovna; Korotkova E. I. Elena Ivanovna (2018, 2018)
Title screen